Stability Analysis of High Jointed Rock Slope with Steep Week Fracture Zone - HUANG Wenhong; ZHANG Jian; LI Longlong; PAN Bing; CHU Weijiang (Renmin Zhujiang)
The failure mode and stability characteristics of the rock slope are mainly determinedby the dominant weak structural plane. Taking the slope with steep week fracture zone at right bankfor a pumped storage power station in Fujian for example, this paper analyzes the failure mode andstability of the slope based on the geological analysis, and combined with discrete unit strengthreduction method. The research results show that: the failure mode of the slope is controlled bythe steep weak fracture zone and the bedding dominant structural plane with low dip angle. Thestability of the natural slope is good, and the slope stability will be decreased by engineeringexcavation. The deformation of the rock mass towards the river valley is large, and the safetyfactor does not meet the requirements of the standard. After reinforcement by prestressed anchorcable, the deformation of the slope is effectively controlled, and the stability of slope meetsthe requirements.